Hengshun Aromatic Vinegar Improves Glycolipid Metabolism in Type 2 Diabetes Mellitus via Regulating PGC-1α/PGC-1β Pathway - Li, Guoquan; Tan, Xuemei; Zhang, Bao; Guan, Linshu; Zhang, Yidan; Yin, Lianhong; Gao, Meng; Zhu, Shenghu; Xu, Lina (Frontiers in Pharmacology, 2021)
Hengshun aromatic vinegar (HSAV), produced by typical solid-state or liquid-state fermentation techniques, is consumed worldwide as a food condiment. HSAV shows multiple bioactivities, but its activity in type 2 diabetes mellitus (T2DM) and possible mechanisms have not been reported. In this study, the effects of HSAV against T2DM were evaluated in insulin-induced HepG2 cells and high-fat diet (HFD) and streptozotocin (STZ) induced T2DM rats. Then, the mechanisms of HSAV against T2DM were explored by Real-time PCR, Western blot, immunofluorescence assays, siRNA transfection and gene overexpression experiments. Results indicated that HSAV significantly improved glucose consumption and reduced triglycerides (TG) contents in metabolic disordered HepG2 cells. Meanwhile, HSAV obviously alleviated general status, liver and kidney functions of T2DM rats, and decreased hyperglycemia and hyperlipidemia, improved insulin resistance, and reduced lipid accumulation in liver. Mechanism studies indicated that HSAV markedly down-regulated the expression of proliferator-activated receptor γ coactivator-1α (PGC-1α), then regulated peroxisome proliferators-activated receptor α (PPAR-α)/protein kinase B (AKT) signal pathway mediated gluconeogenesis and glycogen synthesis. Meanwhile, HSAV significantly up-regulated proliferator-activated receptor γ coactivator-1β (PGC-1β), and subsequently decreased sterol regulatory element binding protein-1c (SREBP-1c) pathway mediated lipogenesis. In conclusion, HSAV showed potent anti-T2DM activity in ameliorating dysfunction of glycolipid metabolism through regulating PGC-1α/PGC-1β pathway, which has a certain application prospect as an effective diet supplement for T2DM therapy in the future.